Local forest governance in Ethiopia: Between legal pluralism and livelihood realities - Till Stellmacher (University of Bonn, Center for Development Research (ZEF), 2013)
Ethiopia's montane rainforests have witnessed high rates of depletion and deforestation in the last decades. The main reasons are expansion and intensification of smallholder agriculture and forestry. Forest governance in Ethiopia is characterized by the complex interaction of factors such as nationalization of land, weak state structures, the persistence of traditional local institutions, and socio-cultural heterogeneity promoted by state-enforced resettlement. This paper aims to contribute to the understanding of forest governance in Ethiopia and the underlying reasons for and variables influencing forest depletion and deforestation by analysing a local institutional arena in a case study approach. The paper is based on local-level empirical field research conducted in the montane rainforests of southwestern Ethiopia. Methodologically, a combination of semi-structured expert interviews with forest users, local traditional decision-makers and representatives of governmental and nongovernmental organizations was used, as well as focus group discussions and visual communication techniques. The paper adopts a historical perspective, reflecting the path-dependent character of local institutions. Historically, the rainforests in the case study area, Koma forest in Kaffa zone, are divided into forest use-right plots individually held by local peasants. The nationalization of all land in Ethiopia in 1975 was a major institutional turning point. By decree, responsibility for forest management was shifted to state bodies. In practice the newly established state bodies never had the necessary resources or expertise to effectively fulfil their tasks. Instead the traditional forest use rights lingered on, backed by local community-initiated institutional systems with a status of 'tolerated illegality'. However, the research findings also indicate that local community-initiated institutional systems are limited to certain forest user groups, and exclude others. This explains their little practical assertiveness, and contributed to the creation of a local-level power vacuum that allows high rates of deforestation and forest degradation.
Keywords: 330; Ethiopia; forest governance; legal pluralism; property rights; iddir